Hypertension, cholesterol and diabetes medication adherence, health care utilization and expenditure in a Medicare Supplemental sample. Issue 35 (3rd September 2021) - Campbell, Patrick J.; Axon, David R.; Taylor, Ann M.; Smith, Karen; Pickering, Matthew; Black, Heather; Warholak, Terri; Chinthammit, Chanadda
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Limited evidence exists regarding the relationships between adherence, as defined in Pharmacy Quality Alliance (PQA) medication adherence measures, health care utilization, and economic outcomes. PQA adherence measures for hypertension, cholesterol, and diabetes are of particular interest given their use in Medicare Star Ratings to evaluate health plan performance. The objective of this study was to assess the relationship between adherence and utilization and cost among Medicare Supplemental beneficiaries included in the aforementioned PQA measures over a 1-year period. Retrospective cohort study. Three cohorts (hypertension, cholesterol, and diabetes) of eligible individuals from the Truven Health MarketScan Commercial Claims and Encounters Research Databases (2009–2015) were used to assess associations between adherence and health care expenditure and utilization for Medicare Supplemental beneficiaries. Generalized linear models with log link and negative binomial (utilization) or gamma (expenditure) distributions assessed relationships between adherence (≥80% proportion of days covered) and health care utilization and expenditure (in 2015 US dollars) while adjusting for confounding variables. Beta coefficients were used to compute cost ratios and rate ratios. Adherence for all 3 disease cohorts was associated with lower outpatient and inpatient visits. During the 1-year study period, adherence was associated with lower outpatient, inpatient, and total expenditures across the cohorts, ranging from 9% lower outpatient costs (diabetes cohort) to 41.9% lower inpatient costs (hypertension cohort). Savings of up to 324.53 per member per month in total expenditure were observed for the hypertension cohort. Our findings indicate adherence is associated with lower health care utilization and expenditures within 1 year.